Rethinking your approach to training for the weight throw - Judge, L. (Track Coach, 2006)
This article explores alternative approaches to developing top hammer throwers under the traditional collegiate track and field system. The author tackles the problems throwing the weight indoors may cause for hammer throwers and how they might be overcome.